Slip energy recovery of a rotor-side field oriented controlled wound rotor induction motor fed by matrix converter - Sunter, Sedat (Pergamon-Elsevier Science Ltd, 2008)
This paper investigates rotor-side field oriented control of a wound-rotor induction motor using the slip energy recovery principle. The proposed drive system uses a matrix converter to transfer the slip energy from the rotor into the mains instead of using ac-dc-ac converter whilst the stator side is fixed to the grid. Operation at both subsynchronous and supersynchronous regions is possible with the proposed drive system. Simulation studies of the proposed doubly fed induction motor drive system verify the good control performance of the system in transient and steady-state conditions. (C) 2008 The Franklin Institute. Published by Elsevier Ltd. All rights reserved.
Keywords: matrix converter; wound-rotor induction motor; vector control; slip recovery